2018
DOI: 10.3390/rs10030483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Storage Variations Estimated from GRACE Data Assimilation and State-of-the-Art Land Surface Models in Australia and the North China Plain

Abstract: The accurate knowledge of the groundwater storage variation (∆GWS) is essential for reliable water resource assessment, particularly in arid and semi-arid environments (e.g., Australia, the North China Plain (NCP)) where water storage is significantly affected by human activities and spatiotemporal climate variations. The large-scale ∆GWS can be simulated from a land surface model (LSM), but the high model uncertainty is a major drawback that reduces the reliability of the estimates. The evaluation of the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 67 publications
(109 reference statements)
2
30
0
Order By: Relevance
“…We have to admit that the method used in this study to derive GWS is imperfect and uncertainties exist. Recently, data assimilation techniques have been proposed to improve the simulation of hydrological models by assimilating the GRACE observation into hydraulic models [65][66][67][68][69]. We will use these new techniques in our future studies to enhance the accuracy of the GWS estimate.…”
Section: Discussionmentioning
confidence: 99%
“…We have to admit that the method used in this study to derive GWS is imperfect and uncertainties exist. Recently, data assimilation techniques have been proposed to improve the simulation of hydrological models by assimilating the GRACE observation into hydraulic models [65][66][67][68][69]. We will use these new techniques in our future studies to enhance the accuracy of the GWS estimate.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new GRACE products based on regional mass concentration (mascon) functions have been developed with constraints applied during the inversion of satellite ranging observations (as opposed to after inversion) to better preserve GRACE signals (Rowlands et al, 2005;Save et al, 2012;Watkins et al, 2015). Direct assimilation of gridded GRACE data, which has been performed in recent studies (Tangdamrongsub et al, 2018;Eicker et al, 2014;Girotto et al, 2016Girotto et al, , 2017Kumar et al, 2016;Tangdamrongsub et al, 2015;Tian et al, 2017;van Dijk et al, 2014), not only preserves more of the observed information but also enables better alignment with existing infrastructures of land surface modeling, which are constructed on regular grids rather than irregular basins. , which is important for continuous drought monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that the quality of GRACE estimates increases with decreasing resolution (i.e. larger areas), they can be of great use to constrain and improve global and regional hydrological models, as proved by many studies (Güntner, 2008;Tangdamrongsub et al, 2018;Werth and Güntner, 2010).…”
mentioning
confidence: 99%